Considerations for the US health-system pharmacist in a world of biosimilars - Andrea Zlatkus; Todd Bixby; Kavitha Goyal (BioExcel Publishing Ltd, 2020)
As numerous biosimilar products are forecast to enter the US market in the coming years, health-system pharmacists will be faced with novel challenges while incorporating them into clinical practice. The current regulatory approval framework and guidance from the US Food and Drug Administration do not address many real-world scenarios that pharmacists will encounter. We provide an overview of the evolving healthcare landscape shaped by the entry of multiple biosimilars, including for a given reference product, and their impact on the healthsystem pharmacist with respect to formulary assessment, implementation, and education of various health-system stakeholders, including patients.